Transjugular intrahepatic portosystemic stent-shunt in the management of portal hypertension. Issue 7 (29th February 2020) - Tripathi, Dhiraj; Stanley, Adrian J; Hayes, Peter C; Travis, Simon; Armstrong, Matthew J; Tsochatzis, Emmanuel A; Rowe, Ian A; Roslund, Nicholas; Ireland, Hamish; Lomax, Mandy; Leithead, Joanne A; Mehrzad, Homoyon; et al.
Abstract : These guidelines on transjugular intrahepatic portosystemic stent-shunt (TIPSS) in the management of portal hypertension have been commissioned by the Clinical Services and Standards Committee (CSSC) of the British Society of Gastroenterology (BSG) under the auspices of the Liver Section of the BSG. The guidelines are new and have been produced in collaboration with the British Society of Interventional Radiology (BSIR) and British Association of the Study of the Liver (BASL). The guidelines development group comprises elected members of the BSG Liver Section, representation from BASL, a nursing representative and two patient representatives. The quality of evidence and grading of recommendations was appraised using the GRADE system. These guidelines are aimed at healthcare professionals considering referring a patient for a TIPSS. They comprise the following subheadings: indications; patient selection; procedural details; complications; and research agenda. They are not designed to address: the management of the underlying liver disease; the role of TIPSS in children; or complex technical and procedural aspects of TIPSS.